Parents - Children Communication on Sexual and Reproductive Health: A Case of Secondary School Students in Kinondoni Municipality, Dar es Salaam (The Journal of Building and Land Development, 2023)
The study on parents - children communication on sexual and reproductive health was done in Kinondoni Dar es Salaam, Tanzania. The motive behind this study was the increased number of youths’ infection with HIV/AIDS, STIs and STDs despite of knowledge provided at school, seminars and social media. Hence, it was necessary to conduct this study believing that parents play a huge role in setting the foundation of different kind of knowledge to their children. The study focused on examining children source of information on sexual and reproductive health, choices of children’ when discussing sexual and reproductive issues and factors hinder parents - children communication on sexual and reproductive health issues. Social Cognitive Theory was used to guide the study. Cross sectional research design was employed in this study. The study found that most of children prefer discussing sexual and reproductive health issues with peers than parents; some of parents are inferior to their children in discussing sexual and reproductive health issues because the children are having high level of education than them; if was to select whom to discuss on sexual and reproductive health issue, most children could prefer female than male parents. The study recommends that professionals including government officials such as community development workers, health workers, psychologists; NGOs, CSOs and other responsible organs should play a role to educate the community specifically parents on the importance of having Parent - children communication on sexual and reproductive health issues. Key words: Communication, parents – children communication, social cognitive theory